English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

x + 3y = 12
–5x – 4y = –16

2007-09-02 17:41:57 · 3 answers · asked by Anonymous in Science & Mathematics Mathematics

3 answers

Multiply the top line by five, and after you distribute you will have:

5x + 15y = 60

Add the first line to the second, the x's will cancel out and you will have...

11y = 44

Divide by 11, and y will be 4

SUBSTITUTE y = 4 in the original equation

x + 3(4) = 12
then solve for X, which is 0

Repeat for the second line, confirm the answer is 0

So X = 0 and Y =4

2007-09-02 17:46:34 · answer #1 · answered by jhannise 2 · 0 0

x = 12 - 3y

substitute for x in the second equation:
-5(12 - 3y) - 4y = -16
-60 + 15y - 4y = -16
11y = 44
y = 4
x = 12 - 3*4 = 0

2007-09-03 00:46:50 · answer #2 · answered by gebobs 6 · 0 0

x = 12 - 3y

-5x - 4y = -16
-5(12 - 3y) - 4y = -16
-60 + 15y - 4y = -16
11y = 44
y = 4

x = 12 - 3(4)
x = 0

(0, 4) is the solution.

2007-09-03 00:45:20 · answer #3 · answered by Anonymous · 0 0

fedest.com, questions and answers